THE MINERALOGICAL, GEOCHEMICAL, AND PETROPHYSICAL ANALYSIS OF SILURIAN-DEVONIAN SHALES OF THE KROH FORMATION: THEIR POTENTIAL FOR HYDROCARBON EXPLORATION - ADAM SHOIEB, MONERA ADAM (2021)
The heterogeneity and complexity of shale gas have become clear as the development of unconventional resources has improved.